THE MAIN WAYS OF ORGANIZING INDEPENDENT EDUCATION. - Yuldasheva Inobat Ashuraliyevna; Usmanova M M (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract: Independent work is one of the forms of learning in which the level of knowledge, skills and competences that are defined in the curriculum of a particular subject must be acquired by students using the recommendations of teaches, This article summarizes information about ways to organize independent education.